Reliability and Validity of the Commitment to Physical Activity Scale for Adolescents - Robbins, Lorraine B.; Ling, Jiying; Wesolek, Stacey M.; Kazanis, Anamaria S.; Bourne, Kelly A.; Resnicow, Ken (American journal of health promotion, 2017)
Purpose. To examine psychometric properties of a Commitment to Physical Activity Scale for Adolescents (CPASA). Design. Two test-retest studies and a prospective study, approved by a university institutional review board, were conducted in midwestern U.S. urban areas. Setting. The first test-retest study occurred in four community centers, the second test-retest study took place in a community school, and the prospective study occurred in eight middle schools. Subjects. To measure commitment at baseline and 1 week later, 51 girls in the first test-retest study completed an original 26-item scale, and 91 in the second test-retest study completed a revised 11-item scale. In the prospective study, 503 girls completed the 11-item scale. Measures. Commitment was measured via the CPASA. After completing the CPASA, girls in the prospective study wore ActiGraph GT3X-plus accelerometers that measured light, moderate, and vigorous physical activity (LMVPA) and moderate to vigorous physical activity (MVPA). Analysis. Internal consistency and test-retest reliability were estimated. Both exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) were conducted to cross-validate the factor structure. Results. For the 11-item CPASA, Cronbach α ranged from .81 to .82, and test-retest reliability was .88. Both EFA and CFA indicated a single factor. The scale was significantly correlated with LMVPA (r = .10) and MVPA (r = .11). Conclusion. The 11-item CPASA demonstrated acceptable reliability and validity with girls.